Poverty Reduction and Growth: Virtuous and vicious circles / Guillermo E. Perry - Perry, Guillermo E. Arias, Omar S. Humberto López, J. Maloney, William F. Serven, Luis (Washington (State) : The World bank, 2006)
Trata sobre la relación entre el crecimiento económico y la reducción de la pobreza.
1. Income poverty 2. Does poverty matter for Grouth?
incluye índice
Col. Admon
Keywords: 1. FROM VICIOUS TO VIRTUOUS CIRCLES 2. HOW DID WE GET GERE?